Clefts and their Relatives. - Reeve, Matthew (Linguistik Aktuell/Linguistics Today., 2012)
Cleft constructions have long presented an analytical challenge for syntactic theory. This monograph argues that clefts and related constructions cannot be analysed in a straightforwardly compositional manner. Instead, it proposes that the locality conditions on modification (for example by a restrictive relative clause) must be reformulated such that they account for the apparent compositionality of DP-internal modification whilst also permitting 'discontinuous' modification of the type which is independently needed for constructions such as relative clause extraposition. The empirical focus.